Analysis of Safety Leadership Styles Based on the Leadership Style Approach and Their Effect on Worker Participation in Mining Safety Implementation - Muhammad Osaegi Restu Amrulloh; Mila Tejamaya (Al-Hijrah Indonesia, 2026)
Worker participation is a critical factor in the successful implementation of the Mining Safety Management System. The level of worker participation is influenced by various factors, including the safety leadership demonstrated by supervisors and managers. This study aimed to analyze the influence of safety leadership styles on worker participation in implementing mining safety at a Private Limited Company. An explanatory sequential mixed-methods design was employed. The quantitative phase used a cross-sectional approach involving 715 respondents selected through proportionate stratified random sampling. Data were analyzed using Spearman correlation and multiple linear regression. The qualitative phase was conducted through in-depth interviews, observations, and focus group discussions to explain and enrich the quantitative findings. The results showed that all dimensions of safety leadership were positively and significantly associated with worker participation, with the strongest relationship observed in task-centered leadership (r = 0.688; p < 0.001). Multivariate analysis revealed that task-centered leadership was the most influential dimension affecting worker participation (β = 0.295; p < 0.001), followed by democratic leadership (β = 0.292; p < 0.001) and relationship-centered leadership (β = 0.200; p = 0.001), while authoritarian leadership was not significantly associated with worker participation (p = 0.372). The regression model explained 49.4% of the variance in worker participation (Adjusted R² = 0.491). Qualitative findings indicated that clear work instructions, consistent safety supervision, two-way communication, worker involvement in decision-making, and follow-up on worker feedback were key factors supporting increased worker participation. This study concludes that safety leadership plays an important role in enhancing worker participation in mining safety initiatives, with task-centered leadership as the most dominant dimension influencing it.